Pengaruh penggunaan kamus digital terhadap pembelajaran bahasa asing (Mandarin) pada mahasiswa Universitas Negeri Malang angkatan 2019 - Fourtuna, Elly Chossy; Aulia, Intan Fitri (2020)
To learn a foreign language requires various supporting objects such as a dictionary. The dictionary is the most effective learning support stuff for getting to know new vocabulary or seeing some vocabulary that we don't know the meaning of and how to pronounce it correctly. In general, a dictionary is in the form of a very thick book and has various sizes. As technology advances, now the dictionary can be accessed via devices and there is no need to carry a printed dictionary that is quite thick in size. So that it causes the use of printed dictionaries to be replaced by the digital dictionary. With digital dictionaries, most people are more interested in learning languages, because of their easier, more interesting, and complete access. Nowadays there are a lot of dictionaries ranging from book form, electronic dictionary, desktop and web dictionary applications